“Embarazo prolongado y su relación con el estado del recien nacido en el hospital apoyo Iquitos “Cesar Garayar García” región Loreto periodo Octubre 1994 – setiembre 1995” - Vásquez Pinedo, Celia Belén (1995)
The present study applied rate and cohort, was in Hospital support period 81 October 1994 to 30 pregnancy prolonged and newborn, its set of relationships between the results obtained and those of other authors, and thus have a ccmocimiento according to our reality. of 2,866 births selected patients with diagnosis of post-term pregnancy by subjected them to interrogation and has criteria for inclusion and to their respective newly born, assessed the results were submitted to the frequency of pregnancy prolonged for FUM was...! -· Ul:-;.' • . J N"Ut:'!...